The Role of Notary in Interbank Credit Take Over - Putri, Ristien Gita Eka; Hafidz, Jawade (Jurnal Konstatering, 2023)
Credit Take Over is the provision of credit facilities by banks/non-banks with the aim of paying off the debtor's debt obligations at a particular bank accompanied by taking over the collateral to serve as collateral for the provision of credit facilities. In practice, loans that are guaranteed by collateral are often carried out by take over. This study aims to determine the regulation of the role of a Notary in interbank credit take over and to know and understand the implementation of the role of a Notary in interbank credit take over. The type of research used is to use empirical juridical methods with the nature of descriptive analysis research. The implementation of this method is to collect data from various literature and legal theory as well as about the role of a Notary in taking over interbank credit. The results of the study show that, according to UUJN No. 2 of 2014 Article 1. Notaries in carrying out their duties and authorities must comply with the regulations in UUJN or Government Regulations regarding Notaries, and must obey and adhere to what is the Notary's code of ethics. The role of a Notary in making authentic deeds, especially those related to authentic Deeds of taking over credit, is an effort to provide legal certainty to the parties. This is where the role of the Notary is in realizing the precautionary principle so that problems do not occur in the future which can harm the parties to the deed, as well as harm the Notary himself. Keywords: Credit; Notary; Take Over.